Drones and targeted killing in the Middle East and Africa an appraisal of American counterterrorism policies - Rinehart, Christine Sixta 1980 (Lexington Books, 2016)
"The use of drone warfare has become a controversial foreign policy weapon to keep the United States safe from further terrorist attacks. This book is an assessment of American targeted killing practices through drone warfare in the Middle East and Africa, including Afghanistan, Iraq, Libya, Pakistan, Somalia, Syria, and Yemen."--Provided by publisher